Analysis of Blackhole Attack in AODV and DS - Niranjan Panda; Binod Kumar Pattanayak (International Journal of Electrical and Computer Engineering (IJECE), 2018)
Mobile Ad-Hoc Networks (MANETs) are supreme ruler and demoralization wireless scheme. MANETs are infrastructure less i.e. their structure is not fixed, and the nodes be able to move about and can leave the network whenever they want. The nodes are to perform as more over router and host. In MANETs, the node can be in contact with every node as their configuration is not fixed and the nodes starts transmitting the packets to each other for the establishment of the connection. To hitch the link, the nodes make use of some routing protocols like Ad-Hoc On Demand Distance Vector (AODV), Dynamic Source Routing (DSR), and DestinationSequenced Distance Vector (DSDV). Security in MANET is the key matter meant for the fundamental utility of network. There are many attacks caused in MANET. Blackhole attack is one that occurs in MANET. A Black hole attack is an attack where the node, which is malicious advertise itself as having the optimal route to the destination and drops all the packets instead of forwarding further to the destination. Here, we have shown the blackhole attack in AODV and DSR. Through simulation we evaluate the performance of the two above protocols under blackhole attack.